Impact of Green Marketing Strategy on Business Performance-Mediating Role of Corporate Image in Construction Industry of Kenya - Muzaffar Hussain Shah (Arthatama: Journal of Business Management and Accounting, 2022)
This article aimed to determine the impact of green marketing strategy on business performance through the mediating role of the corporate image, particularly in the case of the construction industry of Kenya. For this purpose, top management employees from the construction industry of Kenya were contacted and sent a link to the questionnaire (created on Google Forms) to nearly 1000 respondents through social media platforms. A total of 513 appropriate and duly filled questionnaires were received. The study used confirmatory factors Analysis (CFA) in a partial least square structural equation model (PLS-SEM). The study’s findings have suggested that green marketing strategy and corporate image have a positive and significant impact on business performance and that corporate image also plays a positive and significant role in mediating the effect of green marketing strategy on business performance. Therefore, it is recommended for the construction companies of Kenya to use environmentally friendly products and materials to stimulate the customers’ purchase intention and improve corporate and business performance. Meanwhile, further study is suggested over the African region to generalize the findings.